Quartz Crystal Microbalance for viscosity measurement with temperature self-compensation. (May 2019) - Yenuganti, Sujan; Zhang, Chen; Zhang, Haifeng
Highlights: A viscosity measurement system is designed using an AT-cut quartz crystal resonator. Temperature induced frequency shift is compensated by the sensor itself. Beat frequency based temperature compensation technique is employed. The sensor is portable, low cost and can be used for laboratory viscosity testing. Abstract: This paper presents the design, fabrication, and experimental demonstration of a portable viscosity measurement system using an AT-cut quartz crystal resonator with a temperature compensation technique. The proposed sensor is designed to measure viscosity from room temperature to 65 °C with complete temperature compensation. A novel fixture to hold the crystal for the viscosity sensing is designed using CAD (Computer Aided Design) software and a 3D model prototype was fabricated using a 3D printer. Subsequently, the fabricated fixture was integrated with a crystal resonator and tested with various mixtures of glycerol and water solutions each with different viscosities. A beat frequency based temperature measurement and compensation technique was also proposed and has been implemented in the crystal resonator based force measurement system in the literature. The measurement system is portable, simple, and low cost making it convenient for laboratory-based viscosity measurements. The proposed fixture of the measurement system can be altered for real-time monitoring to quantify the viscosity of the continuous flowing aqueous liquids.